PERUBAHAN BUDAYA DALAM TAFSIR AL-QUR’AN (TELAAH TERHADAP PENAFSIRAN MUHAMMAD ABDUH DALAM TAFSIR AL-MANAR) - Imam Muhsin (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2015)
Tafsir al-Quran has the position is very important for the life of the people of Islam and its history. Because, with the interpretation of the procedures against the Qur’an, they could develop a global view of the world, history, meaning, and destiny of man. In other words, all legal norms, ethics, moral, political, and intellectual plucked from textual forms of Scripture through interpretation. The fact that the history and culture of the Muslims are not affected by the Qur’an directly, but rather determined by the interpretation of the results (or, at least, the result of the reading) of the Scriptures, to reaffirm the importance of getting the Tafsir of the Qur’an. The efforts to interpret is done by the historical communities in the cultural environment of the concrete and is constantly changing. The changes that inevitably to be followed by tafsir al-Qur’an so that the messages contained therein can be grounded according adagium: al-Qur’an wa makân zamân likulli shâlihun. In the context of this is the interpretation of Muhammad Abduh in his Tafsir al-Manar can be read as a change of culture, through the process of reintegration of value and reorient the meaning.Keywords: Integration, muslim culture and tafsir al-quran